Zinc phosphide (rodenticide) poisoning: A case report of deliberate self-harm in an eleven-year-old (2022)
Zinc Phosphide(Zn3P2) is a common rodenticide freely available in Nigeria for use against rodents. Occasionally human consumption occurs either accidentally or intentionally with potential consequences of multiorgan toxicity and death. An 11-year-old boy consumed an unknown quantity of zinc phosphide marketed as Push Out with the intention of committing suicide and killing some members of the family as his response to chastisement for a misdemeanour. Patient presented in the hospital 4 days after ingestion of zinc phosphide with a history of profound vomiting and abdominal pain. Laboratory evaluation showed evidence of hepatic dysfunction, acute kidney injury and elevated serum amylase. He was managed conservatively and discharged home after two weeks of admission. We report this case to emphasise the need for Paediatricians to consider ingestion of rodenticides as a differential diagnosis of hepatoxicity and pancreatic enzyme elevation, as well as to highlight the possibility of suicide among children. There is need to control the indiscriminate use of rodenticides, strengthen public health education on poisoning as well as establish Poison Information Centres in our environment.